1
$\begingroup$

Let $$G(z)=\prod_{n=1}^{\infty}\left(1+\frac z n\right)e^{-\frac z n}$$Show that it's an entire function and $G(z-1)=ze^{\gamma}G(z)$ where $$\gamma=\lim_{n\rightarrow \infty}\left(\sum_{k=1}^n\frac 1k-\log n\right)$$

I want to use sum convergence to show the infinite product convergence but here $Re(1+\frac zn)e^{-\frac zn}>0$ does not hold, I was stuck here and I assume it should coincides with the Weierstrass factorization of some entire function with zeros at $-n$, but the Weierstrass factorization take the form $z^me^{g(z)}\Pi E_{p_n}(\frac z {a_n})$ where $g(z)$ should be entire, but here I can't abstract such a function from $e^{-\frac z n}$.

I was preparing for some exam, and this comes from past-year papers.

$\endgroup$
1
$\begingroup$

Uniform convergence on every disk $|z|\le R$. Within this disk $z/n\to 0$ uniformly. Hence $$(1+z/n)e^{-z/n} = (1+z/n)(1-z/n + O(1/n^2)) = 1 + O(1/n^2)$$ with $O$ being uniform. Since $\sum 1/n^2$ converges, the product converges. In particular, $G$ is never zero apart from $z=-1,-2,-3,\dots$.

Functional equation. Let $G_N$ denote the product taken up to $n=N$. Since $$G_N(z) = \prod_{n=1}^{N} \frac{n+z}{n}\cdot \prod_{n=1}^N \exp\left(-\frac{z}{n}\right)$$ and $$G_N(z-1) =z \prod_{n=1}^{N-1} \frac{n+z}{n+1} \cdot \prod_{n=1}^N \exp\left(-\frac{z-1}{n}\right) $$ we have $$\frac{G_N(z-1)}{G_N(z)} = z \frac{N+z}{N} \,\prod_{n=1}^{N-1} \frac{n}{n+1} \cdot \prod_{n=1}^N \exp\left(\frac{1}{n} \right)$$ This simplifies to $$z \frac{N+z}{N} \frac{1}{N} \exp\left(\sum_{n=1}^N \frac{1}{n} \right)$$ which converges to $z e^\gamma$ as $N\to\infty$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.